UNIVERSAL HEALTH COVERAGE IN NIGERIA AND ITS DETERMINANTS: THE CASE OF NATIONAL HEALTH INSURANCE SCHEME - Adebola, Olukemi Grace (Bursa Teknik Üniversitesi, 2020)
The research disaggregated some micro level factors against the National Health Insurance Scheme (NHIS) to determine the accessibility and utilization of Universal Health Coverage (UHC) in Nigeria. Data from 2018 Nigeria Health and Demographic Survey was used and analysed using logistic regression model for the study. The results revealed that only 2.5% Nigerians are covered by NHIS and micro-level factors such as age, region, level of education, wealth index, marital status and household size significantly determined both accessibility and utilization of the scheme. This result indicates that many Nigerians pay Out-of-Pockets (OOP) for healthcare service. Therefore, until due attention is given to these identified micro-level factors as determinants of health insurance, achieving Sustainable Development Goals (SDGs) on UHC by year 2030 becomes a mirage despite huge spending on NHIS by the government.

The research disaggregated some micro level factors against the National Health Insurance Scheme (NHIS) to determine the accessibility and utilization of Universal Health Coverage (UHC) in Nigeria. The results revealed that only 2.5% Nigerians are covered by NHIS and micro-level factors such as age, region, level of education, wealth index, marital status and household size significantly determined both accessibility and utilization of the scheme. This result indicates that many Nigerians pay Out-of-Pockets (OOP) for healthcare service. Therefore, until due attention is given to these identified micro-level factors as determinants of health insurance, achieving Sustainable Development Goals (SDGs) on UHC by year 2030 becomes a mirage despite huge spending on NHIS by the government
UNIVERSAL HEALTH COVERAGE IN NIGERIA AND ITS DETERMINANTS: THE CASE OF NATIONAL HEALTH INSURANCE SCHEME
Keywords: Sociology; Sosyoloji